An update on the distribution of the poorly known flower beetle genus Cymophorus Kirby, 1827 (Coleoptera: Scarabaeidae: Cetoniinae) in Asia - Xu, Hao; Qiu, Jian-Yue (Zootaxa, 2020)
The genus Cymophorus Kirby, 1827 in Asia is represented by the single species C. pulchellus Arrow, 1910. This rare species is traditionally divided into two subspecies, the nominate subspecies from India and C. pulchellus tonkinensis Schein, 1954 from Indochina. While recently, the latter was informally treated as a synonym of C. pulchellus. By examining type material and additional specimens, the differences in the external features between the individuals from the two regions are reconsidered, and the two taxa are probably not identical. Precise localities of C. pulchellus tonkinensis in China are given, and geographic distribution of both subspecies is summarized in a map.